Relayer l’urgence : réflexions autour d’une expérience pédagogique de sciences politiques en dialogue avec les études cinématographiques - Maylis Asté; Matilda Holloway (Les Cahiers de Framespa)
This article proposes some thoughts on the teaching methods of the Experimentation in Political Sciences Master’s degree (SPEAP) that was founded in 2010. Following an interview with Jean-Michel Frodon as well as a critical analysis of the film Leviathan, it questions the ways in which the audiovisual medium is capable of relaying the ecological emergency.